Arterial–Ventricular Coupling with Aging and Disease - Chantler, Paul D.; Lakatta, Edward (Frontiers in Physiology, 2012)
Age is the dominant risk factor for cardiovascular diseases. Understanding the coupling between the left ventricle (LV) and arterial system, termed arterial–ventricular coupling (EA/ELV), provides important mechanistic insights into the complex cardiovascular system and its changes with aging in the absence and presence of disease. EA/ELV can be indexed by the ratio of effective arterial elastance (EA; a measure of the net arterial load exerted on the LV) to left ventricular end-systolic elastance (ELV; a load-independent measure of left ventricular chamber performance). Age-associated alterations in arterial structure and function, including diameter, wall thickness, wall stiffness, and endothelial dysfunction, contribute to a gradual increase in resting EA with age. Remarkably there is a corresponding increase in resting ELV with age, due to alterations to LV remodeling (loss in myocyte number, increased collagen) and function. These age-adaptations at rest likely occur, at least, in response to the age-associated increase in EA and ensure that EA/ELV is closely maintained within a narrow range, allowing for optimal energetic efficiency at the expense of mechanical efficacy. This optimal coupling at rest is also maintained when aging is accompanied by the presence of hypertension, and obesity, despite further increases in EA and ELV in these conditions. In contrast, in heart failure patients with either reduced or preserved ejection fraction, EA/ELV at rest is impaired. During dynamic exercise, EA/ELV decreases, due to an acute mismatch between the arterial and ventricular systems as ELV increases disproportionate compared to EA (≈200 vs. 40%), to ensure that sufficient cardiac performance is achieved to meet the increased energetic requirements of the body. However, with advancing age the reduction in EA/ELV during acute maximal exercise is blunted, due to a blunted increase ELV. This impaired EA/ELV is further amplified in the presence of disease, and may explain, in part, the reduced cardiovascular functional capacity with age and disease. Thus, although increased stiffness of the arteries itself has important physiological and clinical relevance, such changes also have major implications on the heart, and vice versa, and the manner in the way they interact has important ramifications on cardiovascular function both at rest and during exercise. Examination of the alterations in arterial–ventricular coupling with aging and disease can yield mechanistic insights into the pathophysiology of these conditions and increase the effectiveness of current therapeutic interventions.